Cellular Responses to Complex Strain Fields Studied in Microfluidic Devices - Chagnon-Lessard, Sophie (Université d'Ottawa / University of Ottawa, 2018)
Cells in living organisms are constantly experiencing a variety of mechanical cues. From the stiffness of the extra cellular matrix to its topography, not to mention the presence of shear stress and tension, the physical characteristics of the microenvironment shape the cells’ fate. A rapidly growing body of work shows that cellular responses to these stimuli constitute regulatory mechanisms in many fundamental biological functions. Substrate strains were previously shown to be sensed by cells and activate diverse biochemical signaling pathways, leading to major remodeling and reorganization of cellular structures. The majority of studies had focused on the stretching avoidance response in near-uniform strain fields. Prior to this work, the cellular responses to complex planar strain fields were largely unknown. In this thesis, we uncover various aspects of strain sensing and response by first developing a tailored lab-on-a-chip platform that mimics the non-uniformity and complexity of physiological strains. These microfluidic cell stretchers allow independent biaxial control, generate cyclic stretching profiles with biologically relevant strain and strain gradient amplitudes, and enable high resolution imaging of on-chip cell cultures. Using these microdevices, we reveal that strain gradients are potent mechanical cues by uncovering the phenomenon of cell gradient avoidance. This work establishes that the cellular mechanosensing machinery can sense and localize changes in strain amplitude, which orchestrate a coordinated cellular response. Subsequently, we investigate the effect of multiple changes in stretching directions to further explore mechanosensing subtleties. The evolution of the cellular response shed light on the interplay of the strain avoidance and the newly demonstrated strain gradient avoidance, which were found to occur on two different time scales. Finally, we extend our work to study the influence of cyclic strains on the early stages of cancer development in epithelial tissues (using MDCK-RasV12 system), which was previously largely unexplored. This work reveals that external mechanical forces impede the healthy cells’ ability to eliminate newly transformed cells and greatly promote invasive protrusions, as a result of their different mechanoresponsiveness. Overall, not only does our work reveal new insights regarding the long-range organization in population of cells, but it may also contribute to paving the way towards new approaches in cancer prevention treatments.
Keywords: mechanobiology; cyclic stretching; microfluidic device; mechanoresponse; nonuniform strain field; oncogenic transformed cells; microfabrication; strain gradient